Are Antioxidants Useful in Preventing the Progression of Chronic Kidney Disease? - Alfredo G. Casanova; Francisco J. López-Hernández; Laura Vicente-Vicente; Ana I. Morales (MDPI AG, 2021)
Chronic kidney disease (CKD) is a progressive impairment of renal function for more than three months that affects 15% of the adult population. Because oxidative stress is involved in its pathogenesis, antioxidants are under study for the prophylaxis of CKD progression. The objective of this work was to meta-analyze the efficacy of antioxidant therapy in CKD patients and to identify the most effective candidate antioxidants. Our meta-analysis showed that, despite being quite heterogeneous, overall antioxidant therapy apparently reduced CKD progression. Pentoxifylline and bardoxolone methyl demonstrated a robust and statistically significant protection, while other products showed a favorable but non-significant tendency, due to a high interindividual variability. Off-target (i.e., antioxidant-independent) effects, such as body weight reduction and heart failure-associated blood dilution, might totally or partially explain the protection provided by effective antioxidants. This potential pleiotropy introduces uncertainty on the role of oxidative stress in CKD progression and on antioxidant therapy in its prevention, which needs to be further investigated. Independently, identification of factors determining the nephroprotective effect of each candidate on each patient is thus necessary for a prospectively personalized antioxidant therapy. Finally, pentoxifylline should be further explored for the prophylaxis of CKD progression.